Fighting Brand & Main Brand: Analisis Persepsi Konsumen terhadap Bauran Pemasaran Lini Produk PT. Sosro - Trinanda, Okki (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2014)
Marketing mix is one of many marketing strategies that usually used by companies to combine product, price, place and promotion. This strategy is always changing amenable to the competitive condition progress. PT. Sosro is one of many companies thats threatened in this tightened competition. To overcome this obstacle, they decided to launch a product as a fighting brand. The product is later branded Teh Botol FruitTea Sosro that originally used to protect their main product Teh Botol Sosro. One thing interesting about using the strategy with fighting brand is a possibility of predatory, which is the fighting brand that was intent to protect the main brand becomes big and eventually act as a competitor for it’s main brand. This condition is made possible by the growth of fighting brand that is so great and replace the main brand perception on consumers mind. The purpose of this research is to determine wether there is predatory risk by fighting brand towards the main brand of PT. Sosro. Furthermore this research wants to know the consumer perceptions towards product (one of the marketing mix) fighting brand and main brand of PT. Sosro. This research is carried out by distributing questionaires to consumers of both product and tested with T-Test.